Physicochemical characteristics of substrates of the mixture of coir with municipal solid waste compost and with biochar - R.M.A. Machado; H.H. Bui (My University, 2021)
Physicochemical characteristics of substrates of the mixture of coir with municipal solid waste compost and with biochar
Keywords: Giá thể xơ dừa; Compost rác thải; Biochar (Than sinh học)